2002
DOI: 10.1007/s00424-002-0784-2
|View full text |Cite
|
Sign up to set email alerts
|

Calsequestrin expression and calcium binding is increased in streptozotocin-induced diabetic rat skeletal muscle though not in cardiac muscle

Abstract: Altered mechanisms of Ca2+ transport may underlie the contractile dysfunctions that have been frequently reported to occur in diabetic cardiac and skeletal muscle tissues. Calsequestrin, a high-capacity Ca2+-binding protein, is involved in the regulation of the excitation-contraction-relaxation cycle of both skeletal and cardiac muscle fibres. We have investigated the expression of calsequestrin and Ca2+ binding in cardiac and skeletal muscle from streptozotocin-induced diabetic rat. Immunoblotting of microsom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
(75 reference statements)
1
10
0
1
Order By: Relevance
“…Since dystrophin is reduced in diabetic muscle, the ion-regulatory apparatus might also be affected in type 2 diabetes. We could previously show that in a drug-induced animal model of type 1 diabetes the Ca 2+ -binding element calsequestrin is drastically up-regulated, probably compensating for abnormal accumulations of elevated intracellular Ca 2+ levels in diabetic muscle fibres (Howarth et al, 2002). However, screening of diabetic GK muscle samples with a library of monoclonal antibodies to key ion-handling proteins did not detect abnormal expression levels in signalling elements that might be indirectly linked to insulin resistance.…”
Section: Article In Pressmentioning
confidence: 94%
“…Since dystrophin is reduced in diabetic muscle, the ion-regulatory apparatus might also be affected in type 2 diabetes. We could previously show that in a drug-induced animal model of type 1 diabetes the Ca 2+ -binding element calsequestrin is drastically up-regulated, probably compensating for abnormal accumulations of elevated intracellular Ca 2+ levels in diabetic muscle fibres (Howarth et al, 2002). However, screening of diabetic GK muscle samples with a library of monoclonal antibodies to key ion-handling proteins did not detect abnormal expression levels in signalling elements that might be indirectly linked to insulin resistance.…”
Section: Article In Pressmentioning
confidence: 94%
“…CASQ1 binds and releases large quantities of Ca 2ϩ rapidly through its high capacity (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) per CASQ molecule) and relatively low-affinity interactions with Ca 2ϩ (28,45). Howarth et al (31) investigated the expression of CASQ and Ca 2ϩ binding in cardiac and skeletal muscle from the streptozotocininduced diabetic rat and found no significant changes in heart but an increase in the relative abundance of CASQ and CASQ-like proteins in skeletal muscle. Together, these data suggest that CASQ1 may play an important role in insulin-and/or contraction-stimulated glucose transport.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium release from the sarcoplasmic reticulum into the cytosol has been shown to regulate GLUT4 expression (29) and glucose transport in muscle (30). Furthermore, Howarth et al (31) reported that CASQ1 expression and calcium binding is increased in streptozotocin-induced diabetic rat skeletal muscle. We hypothesized that variation in CASQ1 may affect insulin action on glucose uptake and glycogen synthesis in skeletal muscle and thus type 2 diabetes susceptibility.…”
mentioning
confidence: 99%
“…Examples of differentially expressed genes previously associated with obesity and T2D included complement component 1, r component (C1r), calsequestrin (Casq1) and secreted protein, acidic, cysteine-rich protein (Sparc). [25][26][27][28] Additional bioinformatics identified four candidate genes not previously associated with metabolic disease for further study. These genes were sushi domain containing 2 (Susd2, NM_019601), collagen and calcium-binding EGF domains 1 (Ccbe1, NM_133459), periostin (Postn, NM_006475) and decorin (Dcn, NM_133503).…”
Section: Development Of Sst In Conjunction With Microarraymentioning
confidence: 99%